2022
DOI: 10.2147/opth.s384360
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Light Therapy in Association with Intense Pulsed Light for Meibomian Gland Dysfunction

Abstract: Purpose To study the clinical benefit of low-level light therapy when associated with intense pulsed light for the treatment of meibomian gland dysfunction. Methods An observational study. Two groups of patients that were treated with IPL were considered: group 1 (31 subjects, 62 eyes), intense pulsed light followed by low-level light therapy and group 2 (31 subjects, 62 eyes) intense pulsed light alone. In both groups, treatments were performed in 3 sessions and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Additionally, in Group 1 and Group 2, there was an increase in the outflow of meibomian glands, as indicated by the LLT improvement. Marques et al [14] previously reported these changes. Improvement in LLT was not present in Group 3, indicating that Thermaeye Plus® may have a less beneficial effect on this parameter when compared to other IPL devices.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, in Group 1 and Group 2, there was an increase in the outflow of meibomian glands, as indicated by the LLT improvement. Marques et al [14] previously reported these changes. Improvement in LLT was not present in Group 3, indicating that Thermaeye Plus® may have a less beneficial effect on this parameter when compared to other IPL devices.…”
Section: Discussionmentioning
confidence: 79%